2014
DOI: 10.1037/a0037221
|View full text |Cite
|
Sign up to set email alerts
|

When the customer is unethical: The explanatory role of employee emotional exhaustion onto work–family conflict, relationship conflict with coworkers, and job neglect.

Abstract: We integrate deontological ethics (Folger, 1998, 2001; Kant, 1785/1948, 1797/1991) with conservation of resources theory (Hobfoll, 1989) to propose that an employee's repeated exposure to violations of moral principle can diminish the availability of resources to appropriately attend to other personal and work domains. In particular, we identify customer unethical behavior as a morally charged work demand that leads to a depletion of resources as captured by employee emotional exhaustion. In turn, emotionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 104 publications
(202 reference statements)
4
67
1
Order By: Relevance
“…Consistent with previous empirical studies documenting the effects of resource depletion, customer mistreatment has been linked with employee sabotage (Shao & Skarlicki, 2014;Wang et al, 2011), incivility toward customers, job demands (van Jaarsveld, Walker, & Skarlicki, 2010), withdrawal (e.g., absences, Grandey et al, 2004), reduced performance (e.g., Sliter, Sliter, & Jex, 2012), and burnout (e.g., Ben-Zur & Yagil, 2005;Dormann & Zapf, 2004;Grandey et al, 2007;Greenbaum, Quade, Mawritz, Kim, & Crosby, 2014). For example, Wang et al (2011), using a sample of call center employees, reported that customer mistreatment was positively related to employee sabotage and this positive association was mitigated by job tenure (i.e., cognitive resource) and service rule commitment (i.e., motivational resource).…”
Section: Customer Mistreatment As a Resource-depleting Eventsupporting
confidence: 51%
“…Consistent with previous empirical studies documenting the effects of resource depletion, customer mistreatment has been linked with employee sabotage (Shao & Skarlicki, 2014;Wang et al, 2011), incivility toward customers, job demands (van Jaarsveld, Walker, & Skarlicki, 2010), withdrawal (e.g., absences, Grandey et al, 2004), reduced performance (e.g., Sliter, Sliter, & Jex, 2012), and burnout (e.g., Ben-Zur & Yagil, 2005;Dormann & Zapf, 2004;Grandey et al, 2007;Greenbaum, Quade, Mawritz, Kim, & Crosby, 2014). For example, Wang et al (2011), using a sample of call center employees, reported that customer mistreatment was positively related to employee sabotage and this positive association was mitigated by job tenure (i.e., cognitive resource) and service rule commitment (i.e., motivational resource).…”
Section: Customer Mistreatment As a Resource-depleting Eventsupporting
confidence: 51%
“…For example, in line with the idea that emotionally exhausted employees have fewer resources to attend to family roles and are less motivated to self-regulate effectively, Greenbaum et al (2014) found that emotional exhaustion predicted work-family conflict. Similarly, Liu et al (2015) found that emotional exhaustion due to work was associated with displaced aggression towards family members in the evening.…”
Section: The Work and Home Consequences Of Emotional Exhaustionmentioning
confidence: 86%
“…For example, in line with the idea that emotionally exhausted employees have fewer resources to attend to family roles and are less motivated to self‐regulate effectively, Greenbaum et al. () found that emotional exhaustion predicted work–family conflict. Similarly, Liu et al.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…These behavioral expectations have been woven into the fabric of today's society, such that generally accepted moral norms tend to exist (Cropanzano, Goldman, & Folger, ; Folger, , ; Folger & Skarlicki, ; Greenbaum, Quade, Mawritz, Kim, & Crosby, ). People abide by generally accepted moral norms to keep from infringing on another person's “playing field,” with people then expecting others to play by the same “rules of the game” (Folger, , ).…”
Section: Theoretical Overview and Hypothesesmentioning
confidence: 99%